“You Have to Accept the Pain”: Body Callusing and Body Capital in Circus Aerialism - Walby, Kevin; Stuart, Shawn (Qualitative Sociology Review, 2021)
Little sociological research has examined the work of circus aerialists. Drawing from interviews with 31 circus aerialists in Canada, we explore what aerialists say about their bodies. Circus aerialism is an intense form of physical work, and aerialists endure intense pain during training and performance. Engaging with sociologies of the body and injury, we examine how body capital is generated, maintained, and lost in the career of the aerialist, as well as how injury accelerates this process. Injury and “aging out” of the circus are prominent themes in what aerialists say about their bodies. Arguing that circus aerialism is an undervalued form of work in which risk accumulates in aerialist bodies, we explore how aerialist bodies provide tacit cues about how to avoid injury and when to consider retirement. In the conclusion, we explain how this work contributes to sociologies of the body and circus.